The Concepts of Work and Decent Work in Relationship With Self-Efficacy and Career Adaptability: Research With Quantitative and Qualitative Methods in Adolescence - Zammitti, Andrea; Magnano, Paola; Santisi, Giuseppe (Frontiers in Psychology, 2021)
The way people make career choices is often influenced by their idea of work. Alongside this concept, there is the idea of decent work which takes the form of the opportunity, for men and women, to have productive, equal, safe, and rights-based work. We have conducted a study on these two concepts with a group of Italian adolescents, using both quantitative and qualitative methods. We found that most of the participants consider work as a mean to obtain economic benefits and satisfy certain values, and decent work as characterized by the respect for rights and duties and economic benefits; a part of the participants fails in giving a definition of decent work or gives a negative definition of it. We deepened the study through quantitative analyses that revealed that those who have a more complex view of work and decent work also have higher levels of self-efficacy and career adaptability. These findings are discussed in the light of previous research and from a perspective that intends to give a contribution to career counselling practices.